Clinical Efficacy of Routinely Administered Belimumab on Proteinuria and Neuropsychiatric Lupus - Plüß, Marlene; Tampe, Björn; Niebusch, Noah; Zeisberg, Michael; Müller, Gerhard A.; Korsten, Peter (Frontiers in Medicine, 2020)
Background and Objectives Belimumab (BEL) is a monoclonal antibody approved for the treatment of active systemic lupus erythematosus (SLE), but not for lupus nephritis (LN) and neuropsychiatric systemic lupus erythematosus (NPSLE). We aimed to assess BEL’s effects on these severe, potentially life-threatening manifestations. Methods Retrospective observational cohort study using routine clinical data in a case series of patients with SLE receiving BEL. Results 16 patients received BEL therapy for active SLE. Nine were excluded because they had no LN or NPSLE. Six suffered from LN, and one patient had NPSLE. All LN patients received BEL in addition to standard therapy, including glucocorticoids, hydroxychloroquine, and mycophenolate mofetil in five cases, and tacrolimus in one case. Three patients with proteinuria >1000 mg/g creatinine responded well (one complete, two partial renal responses); all other patients had decreasing proteinuria and a reduction in anti-dsDNA levels. The patient with NPSLE who had failed previous therapies had persistent clinical improvement of cutaneous and neuropsychiatric manifestations. There was one mild allergic reaction and one lower respiratory tract infection, but no other adverse events. One patient discontinued therapy due to a lack of improvement in clinical symptoms, another because of clinical remission. Conclusions In our series, BEL led to a decrease of proteinuria in patients with proteinuria of more than 1000 mg/g creatinine despite SoC treatment and led to a marked clinical improvement in one patient with NPSLE. No adverse events were observed. Routinely administered BEL shows clinical efficacy on non-approved manifestations, but careful patient selection is warranted.